The nightmare of turnover intention for companies in Indonesia - Suyono, Joko; Dwi Ratmawati, Anis Eliyana, (Opción, 2020)
Every company certainly expects its employees to focus on working in the company by devoting all their abilities, knowledge, expertise and time. Working focus of employees will be disturbed when employees have the intention to move, turnover intention, to work elsewhere. Turnover intention is a very serious problem for the company, because turnover intention will cause a very large loss for the company, causing a very large expense for the company. This is qualitative research and the purpose of this research is to analyze the effects of turnover intention and to find solution to turnover intention. In-depth interview techniques was used to get the data